Myeloid cell-specific sirtuin 6 deficiency delays wound healing in mice by modulating inflammation and macrophage phenotypes - Koo, Jeung-Hyun; Jang, Hyun-Young; Lee, Youngyi; Moon, Young Jae; Bae, Eun Ju; Yun, Seok-Kweon; Park, Byung-Hyun (Experimental & molecular medicine, 2019)
We recently reported that myeloid cell-expressed sirtuin 6 (Sirt6) plays a crucial role in M1 macrophage polarization and chemotaxis. Given the prominent role of macrophages during wound repair and macrophage heterogeneity, we hypothesized that a Sirt6 deficiency in myeloid cells would delay skin wound closure by affecting the phenotypes of macrophages in wounds. To address this question, a full-thickness excisional lesion was made in the dorsal skin of myeloid cell-specific Sirt6 knockout (KO) and wild-type mice. Wound closure was delayed in the KO mice, which exhibited less collagen deposition, suppressed angiogenesis, and reduced expression of wound healing-related genes compared to the wild-type mice. Using immunohistochemical, flow cytometric, and gene-expression analyses of macrophage subpopulations from wound tissue, we identified increased infiltration of M1 macrophages with a concomitant decrease in M2 macrophage numbers in the KO mice compared to the wild-type mice. Consistent with the in vivo wound closure defects observed in the KO mice, keratinocytes and fibroblasts treated with KO macrophage-derived conditioned medium migrated slower than those treated with wild-type macrophage-derived conditioned medium. An analysis of downstream signaling pathways indicated that impaired Akt signaling underlies the decreased M2 phenotypic switching in KO mice. These results suggest that a macrophage phenotypic switch induced by Sirt6 deficiency contributes to impaired wound healing in mice. Wound healing: Protein deficiency hinders repair The loss of a protein involved in regulating white cell populations at wound sites can delay healing. Macrophages, a type of white blood cell, are crucial to wound healing. The M1 type of macrophage triggers initial inflammation, consumes damaged tissues, and secretes other molecules that help healing. M1 cells switch to the M2 type during the later stages of wound repair. Seok-Kweon Yun and Byung-Hyun Park at Chonbuk National University Medical School, Jeonju, South Korea, and co-workers examined macrophage phenotypes in wounds, focusing on a protein involved in macrophage type called sirtuin 6 (Sirt6). They compared wound healing responses in wild type mice and those without myeloid Sirt6. In myeloid Sirt6-deficient mice, increased levels of M1 macrophages induced higher levels of inflammation. There was also failure in M2 phenotypic switching in myeloid Sirt6 KO mice, which further delayed wound healing.